Prevalence and associated risk factors of trematode infections in equids from selected practices in Gauteng, South Africa - Viljoen, Adrienne (University of Pretoria, 2023)
Dissertation (MSc (Companion Animal Clinical Studies))--University of Pretoria, 2022.